The efficacy and safety of a combined multipolar radiofrequency with pulsed electromagnetic field technology for the treatment of vaginal laxity: a double-blinded, randomized, sham-controlled trial - Wattanakrai P. (2023)
Non-invasive vaginal rejuvenation with radiofrequency (RF) and lasers devices have gained popularity, but well-designed studies confirming their effectiveness are lacking. The aim of this study was to compare the efficacy and safety of a multipolar RF and pulsed electromagnetic field-based device (PEMF) versus sham for vaginal laxity. Thirty-two premenopausal females with ≥ 1 vaginal delivery and self-reported vaginal laxity were randomized into 2 groups: active (RF + PEMF) and sham. Both groups received 3 vaginal treatments at 3-week interval. The Vaginal Laxity Questionnaire (VLQ), perineometer measurements, and Brink score were conducted at baseline, 4, and 12 weeks after treatments. Pre and post-treatment vaginal histology, Female Sexual Function Index (FSFI), subjects’ satisfaction, pain, and adverse events were assessed. The active group VLQ scores increased and were significantly better than the sham group (p < 0.001). At the final follow-up, 50% of the active group reported no vaginal laxity (VLQ > 4) versus 12% in the sham group (p = 0.054). In the active group, all domains of perineometer measurements and Brink scores (p < 0.001), FSFI scores (p < 0.05), and patients’ satisfaction (p < 0.001) were significantly increased and higher in the active group. Mild adverse effects including pain and burning sensation were not different between groups except for itch which was significantly higher in the sham arm (p = 0.014). Histology after RF + PEMF treatments demonstrated neocollagenesis, neoelastogenesis, and neoangiogenesis. In conclusion, combination RF + PEMF therapy was safe, improved vaginal laxity, strengthened pelvic floor muscles, and improved female sexual function for at least 12-week post-procedures with confirmed histological improvements. This study was registered on the Thai Clinical Trials Registry, TCTR20200803002 on 2020–07-30 “retrospectively registered.”